2019
DOI: 10.1038/s41598-019-49075-3
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal payoff variations and the evolution of cooperation in social dilemmas

Abstract: Varying environmental conditions affect relations between interacting individuals in social dilemmas, thus affecting also the evolution of cooperation. Oftentimes these environmental variations are seasonal and can therefore be mathematically described as periodic changes. Accordingly, we here study how periodic shifts between different manifestations of social dilemmas affect cooperation. We observe a non-trivial interplay between the inherent spatiotemporal dynamics that characterizes the spreading of cooper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 86 publications
2
29
0
Order By: Relevance
“…It is worth noting that the reported cooperator supporting mechanism fits nicely to those observations where the introduced strategy-neutral rule has biased impact on the strategy invasion of competing strategies [44,45,46,47,48,49]. Hence these mechanisms provide an alternative way to understand to original enigma and explain why cooperation may prevail among selfish agents.…”
Section: Discussionsupporting
confidence: 78%
“…It is worth noting that the reported cooperator supporting mechanism fits nicely to those observations where the introduced strategy-neutral rule has biased impact on the strategy invasion of competing strategies [44,45,46,47,48,49]. Hence these mechanisms provide an alternative way to understand to original enigma and explain why cooperation may prevail among selfish agents.…”
Section: Discussionsupporting
confidence: 78%
“…We note that the simultaneous usage of different games was already used by some previous works 47 , 48 . But in these cases the application of diverse payoff elements was a predefined microscopic rule which was assigned to specific players or the usage of alternative payoff elements were the subject of a time-course 49 53 . In our present case, however, the application of different payoff elements is the consequence of a natural evolutionary process which is driven by an individual imitation procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In EGT, heterogeneity can be related to different aspects of a game, e.g., incentives, interaction topology, learning rates, and dynamics. Previous investigations, such as [22,29,[33][34][35][36][37][38], showed that heterogeneity can support cooperative behaviors in many competitive scenarios. At the same time, other studies such as [39] reported that heterogeneous networks do not promote cooperation when humans play the prisoner's dilemma.…”
Section: Introductionmentioning
confidence: 99%
“…One way to study the influence of such random variations is to represent each different environmental condition as a new factor in the equations of a model. Following this method, many authors have made important advances in the understanding of how a number of conditions can drive the system dynamics, such as resource heterogeneity [46], different behaviors [47,48], seasonal variations [33], diverse learning rates [49], different death rates [50], interaction topologies [51], and so on. However, another way to understand these phenomena is to study the behavior of a population whose evolution can be affected by a payoff matrix constantly perturbed by stochastic noise with zero mean value [52][53][54], regardless of its origin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation